Assessing the effect of sound complexity on the audiotactile cross-modal dynamic capture task. - Occelli, V; Spence, C; Zampini, M (2010)
Neurophysiological and behavioural evidence now show that audiotactile interactions are more pronounced for complex auditory stimuli than for pure tones. In the present study, we examined the effect of varying the complexity of auditory stimuli (i.e., noise vs. pure tone) on participants' performance in the audiotactile cross-modal dynamic capture task. Participants discriminated the direction of a target stream (tactile or auditory) while simultaneously trying to ignore the direction of a distracting auditory or tactile apparent motion stream presented in a different sensory modality (i.e., auditory or tactile). The distractor stream could be either spatiotemporally congruent or incongruent with respect to the target stream on each trial. The results showed that sound complexity modulated performance, decreasing the accuracy of tactile direction judgements when presented simultaneously with noise distractors, while facilitating judgements of the direction of the noise bursts (as compared to pure tones). Although auditory direction judgements were overall more accurate for noise (than for pure tone) targets, the complexity of the sound failed to modulate the tactile capture of auditory targets. These results provide the first demonstration of enhanced audiotactile interactions involving complex (vs. pure tone) auditory stimuli in the peripersonal space around the hands (previously these effects have only been reported in the space around the head).